Comparison of screening indicators for different types of thalassemia carriers in Hunan Province - Tang, Hua; Yu, Rong; Yu, ZiYin; Xi, Hui (Journal of Medical Biochemistry, 2023)
Backgroud: Carrier screening is the most effective method to block the occurrence of thalassemia. However, due to differences in race and genotype, MCV, MCH, HbA2 and other indicators are far from each other. The purpose of this study is to evaluate the common screening indicators of α, β and αβ-compound thalassemia carriers in Hunan Province, and try to use the relevant formulas in the existing literature to predict and distinguish different types of thalassemia carriers.Methods: Receiver operating characteristic curve (ROC curve) combined with Youden index was utilized to analyze results of blood routine examination, hemoglobin electrophoresis, and literature-related formulas for 1111 α-thalassemia carriers, 464 β-thalassemia carriers and 24 αβ-thalassemia carriers.Results: For α-thalassemia carriers, no matter which screening index or formula, the screening efficiency was not ideal. For β-thalassemia minor carriers, RBC, RDW_CV, Hb_A2, Hb_F and formula 5-7 could be used, and for compound thalassemia, RBC, RDW_CV, Hb_A2 and formula 5-6 are suitable. Hb_A2 has high efficiency in the screening of β-thalassemia minor and αβ-thalassemia. For the screening of β-thalassemia minor, if the cut-off value of HbA2 is set to 3%, the detection rate of 93.32% can be obtained at the positive rate of 9.6%, and if it is set to 3.15%, the detection rate can also reach 81.68% at the positive rate of 2.89%. For αβ-thalassemia, if the cut-off value of HbA2 is set to 3%, the detection rate of 95.83% can be obtained under the positive rate of 8.08%.Conclusions: Different screening indicators and formulas have different efficiencies for different thalassemia carriers. α-thalassemia carriers are easily missed by screening indicators or corresponding formulas. HbA2 is a better screening indicator for both β-thalassemia minor carriers and αβ-thalassemia carriers, and formulas 5, 6, and 7 are suitable for β-thalassemia minor carriers, and formulas 5 and 6 are better for αβ-thalassemia carriers. To fully and objectively understand each screening index, data support has been provided for clinical and laboratory tests.